2020
DOI: 10.1039/d0ra90049d
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Role of polysilicon in poly-Si/SiOx passivating contacts for high-efficiency silicon solar cells

Abstract: Correction for ‘Role of polysilicon in poly-Si/SiOx passivating contacts for high-efficiency silicon solar cells’ by HyunJung Park et al., RSC Adv., 2019, 9, 23261–23266. DOI: 10.1039/c9ra03560e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Typically, the roles of poly-Si include: (1) contact, since varying the poly-Si doping concentration may alter Φ m and result in varying selectivity; (2) acting as a barrier against metallization and in-diffusion, preventing SiO x from being destroyed and avoiding damaging the passivation properties; (3) gettering, enhancing the bulk quality; and (4) providing a field effect, resulting in the formation of a charge-rich area on the Si surface which can repel one kind of carrier. 108…”
Section: Passivation Stacks: a Comprehensive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the roles of poly-Si include: (1) contact, since varying the poly-Si doping concentration may alter Φ m and result in varying selectivity; (2) acting as a barrier against metallization and in-diffusion, preventing SiO x from being destroyed and avoiding damaging the passivation properties; (3) gettering, enhancing the bulk quality; and (4) providing a field effect, resulting in the formation of a charge-rich area on the Si surface which can repel one kind of carrier. 108…”
Section: Passivation Stacks: a Comprehensive Analysismentioning
confidence: 99%
“…Numerous studies on the fabrication of TOPCon structures have recently revealed new approaches for minimizing parasitic absorption losses associated with the poly-Si layer. 108 Etching the poly-Si layer, using suitable doping profiles or techniques, and adjusting the annealing processes can all contribute significantly to increasing the performances of TOPCon solar cells.…”
Section: Passivation Stacks: a Comprehensive Analysismentioning
confidence: 99%